HUBUNGAN KUALITAS TIDUR DENGAN INDEKS MASSA TUBUH PADA SISWA DI SMA NEGERI 1 GURU LOMBOK KALAWAT - Tangkuman, Pricilia; Fredrik Makadada; Deviana Munthe (JURNAL ILMIAH KESEHATAN MANADO, 2025)
Background: Adolescents are a group that is vulnerable to nutritional problems. If food intake exceeds nutritional needs and lack of physical activity results in the accumulation of body fat and will eventually become obese. Sleep quality also plays a role in determining nutritional status. Quality sleep can affect nutritional status especially against the incidence of obesity, and can refer to hormonal and metabolic changes that lead to weight gain and obesity. The purpose of the study was to determine the relationship between sleep quality and Body Mass Index (BMI) in students at SMA Negeri 1 Guru Lombok Kalawat. This research was conducted at SMA Negeri 1 Guru Lombok Kalawat with a sample of 75 respondents. Sleep quality data was collected using the Pittsburgh Sleep Quality Index (PSQI) questionnaire while the body mass index was calculated using BMI and classified using the WHO Growth Standards. The results of the study used the analysis of chi-square test data that the relationship between sleep quality and body mass index with a correlation coefficient value of 0.564 > 0.05 which means that there is no relationship between sleep quality and body mass index in students of SMA Negeri 1 Guru Lombok Kalawat.